The crystal structure of 2,2′-((1E,1′E)-(naphthalene-2,3 diylbis(azanylylidene)) bis(methanylylidene))bis(4-methylphenol), C26H22N2O2 - Ndlangamandla Nqobile (Zeitschrift für Kristallographie - New Crystal Structures, 2022)
C26H22N2O2, monoclinic, P21/n (No. 14), a = 6.2362(2) Å, b = 16.3148(6) Å, c = 20.0521(7) Å, β = 94.308(1)°, V = 2034.38(12) Å3, Z = 4, Rgt(F) = 0.0439, wRref(F2) = 0.1088, T = 173 K.